Analisis Pengendalian Persediaan Bahan Kain di UMKM IBS Menggunakan Metode Peramalan dan EOQ - Teguh Imansyah; Deny Andesta (G-Tech: Jurnal Teknologi Terapan, 2024)
IBS MSME is a business in the field of home industry manufacturing. The products made are baby sofas, baby bedding, etc. By using the main fabric raw materials, namely tetron, cotton, and knitting. However, excessive purchases and material shortages lead to stock of some fabric materials, which makes it difficult to predict future production quantities. This study aims to determine the company's order quantity and total inventory costs with forecasting methods and economic order quantities. In the TIC calculation, the TIC EOQ results obtained have an economic cost for tetron fabric material of Rp. 10.970 while the Company's TIC is Rp. 51.387. The results of forecasting tetron fabric material amounted to 530/m, cotton amounted to 523/m, and knitting amounted to 514/m. While the results of the EOQ calculation obtained the value of tetron fabric material of 50/m, cotton of 50/m, and knitting of 50/m.